Inventiveness as a Driver of Small and Medium-Sized Business Profitability in South Africa: A Quantile Regression Method - ALIAMUTU, Kansilembo Freddy; MKHIZE, Msizi (PT Keberlanjutan Strategis Indonesia, 2024)
In South Africa, inventiveness is a critical factor in expansion and growth, and small and medium-sized businesses have been designated as tools for achieving the societal and economic objectives and innovation outlined in the National Development Plan. The aim of this research is to look at the impact of inventiveness on small and medium-sized profitability in South Africa. The quantile regression method was utilised in empirical studies to explore the influence of inventiveness on enterprise profitability across different sales stages. The research was based on data from the World Bank's business questionnaire. The research results showed that expenses on development and research had a positive and substantial influence on profitability for businesses with greater sales (fast expansion or bigger enterprises). Existing proof demonstrates that incorporating new items and services boosts profitability for businesses with low progress or tiny businesses. Based on empirical evidence, inventiveness is essential for the growth and development of small and medium-sized businesses. Smaller or low-growth businesses don't have the ability to make expenditures on R&D because of a shortage of funds, which could contribute to their low chances of surviving. Considering the significant cash investment needed for R&D expenditures, additional support could be offered to smaller businesses in less powerful sales expansion. Because of a lack of funding for R&D, smaller businesses are being driven to create new items and production procedures that do not require big financial commitments.